How important is a regional free trade area for Southern Africa?: Potential impacts and structural constraints - Nin-Pratt, Alejandro; Diao, Xinshen; Bahta, Yonas (International Food Policy Research Institute, 2009)
We develop a detailed trade analysis to assess the potential welfare impacts of a free trade agreement (FTA) on the agricultural sector of southern African countries and to determine opportunities and challenges faced by the region as a consequence of the agreement. Our approach combines an in-depth look at the current trading patterns of southern African countries with the application of a partial equilibrium analysis that uses bilateral trade data at the four-digit standard international trade classification (SITC) level for 193 agricultural industries in 14 southern African countries. Low diversification of agricultural exports in most southern African countries seems to be a major constraint for promoting regional trade. In most countries, overall welfare effects of an FTA would be positive but small. Inefficient agricultural producers with a regional comparative advantage for agriculture would benefit from trade creation with the rest of the world. Welfare results for regional importers would be negative because of increased imports from inefficient regional producers. These results suggest that the region should be looking at regional policies and interventions beyond trade arrangements, such as those targeting investment, agricultural productivity, and diversification, to enhance benefits of regional trade liberalization.